2008
DOI: 10.1093/occmed/kqn008
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and health in a seafaring population

Abstract: Seafarers' fatigue could impact on safety within the industry and may be linked to longer term individual ill-health. It can only be addressed by considering how multiple factors combine to contribute to fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 14 publications
3
99
0
1
Order By: Relevance
“…One thing that can be confirmed from the reviewed studies is that they support the general agreement of other researchers in the field, that long working hours increase the risk of fatigue, accident and ill health [13]. However, fatigue is a complex problem, and that factors causing fatigue are not equal in "weight" and that there is a positive association between number of risk factors and increased fatigue [23,26]. Fatigue is also the strongest single risk factor that was positively associated with decreased cognitive performance and health outcomes, accounting for 10-14% of the variance.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…One thing that can be confirmed from the reviewed studies is that they support the general agreement of other researchers in the field, that long working hours increase the risk of fatigue, accident and ill health [13]. However, fatigue is a complex problem, and that factors causing fatigue are not equal in "weight" and that there is a positive association between number of risk factors and increased fatigue [23,26]. Fatigue is also the strongest single risk factor that was positively associated with decreased cognitive performance and health outcomes, accounting for 10-14% of the variance.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, after categorising the factors it was found that more organisational factors were associated with acute fatigue, while long term fatigue was more associated with psychosocial work characteristics [26].…”
Section: Discussionmentioning
confidence: 99%
“…", Sampson addresses the issue of seafarer health and welfare conditions. Seafarer health and welfare remains an issue of concern, since occupational risks in shipping exceed those encountered in many onshore occupations (Nielsen and Roberts, 1999;Bloor et al, 2000;Wadsworth et al, 2008;Ellis et al, 2010). Members of the United Nations' International Labour Organization (ILO) agreed the Maritime Labour Convention (MLC) in 2006, which regulates (a) minimum requirements for shipfarers to work on a ship, (b) conditions of employment, (c) accommodation, recreational facilities, food, and catering, (d) health protection, medical care, welfare, and social security protection, as well as (e) compliance and enforcement (ILO, 2016).…”
Section: The Special Issuementioning
confidence: 99%
“…Lack of sleep, poor sleep quality, long working hours, long-term job, work outside of biorhythms, insufficient rest between work periods, excessive workload, noise, heat, vibration, the difficulties with movement, dehydration, boring or repetitive work, time and climate zones change, inaccessible medical professionals, irregular sexual life, social exclusion and others leads to chronic fatigue, poor work performance, decreased safety, increase in chronic disease and depression risk (1). Wadsworth et al (2008) established links between seamen work characteristics and experiences of fatigue and sickness. There is a positive correlation between fatigues experience and cognitive weakness, psychological distress and general health (2).…”
Section: Introductionmentioning
confidence: 99%
“…Wadsworth et al (2008) established links between seamen work characteristics and experiences of fatigue and sickness. There is a positive correlation between fatigues experience and cognitive weakness, psychological distress and general health (2). Each second seaman experience of psycho-emotional strain (3) which affects cardiovascular system and worsens mental condition, it is important to find cost-effective and efficient means to minimize the risk for seafarers health and restore good health (4).…”
Section: Introductionmentioning
confidence: 99%